Highly sensitive simultaneous electrochemical determination of myricetin and rutin via solid phase extraction on a ternary Pt@r-GO@MWCNTs nanocomposite - Satar Tursynbolat; Yrysgul Bakytkarim; Jianzhi Huang; Lishi Wang (Elsevier, 2019)
The simultaneous electrochemical determination of myricetin and rutin remains a challenge due to their indistinguishable potentials. To solve this problem, we constructed a ternary platinum nanoparticle, reduced graphene oxide, multi-walled carbon nanotubes (Pt@r-GO@MWCNTs) nanocomposite via a facile one-pot synthetic method. Under the optimized conditions, the ternary Pt@r-GO@MWCNTs nanocomposite exhibited good electrocatalytic activity toward myricetin and rutin via solid phase extraction and excellent performance for the simultaneous determination of myricetin and rutin. The oxidation peak current of myricetin was proportional to its concentrations in the range of 0.05-50 μM with a detection limit of 0.01 μM (S/N = 3). The linear range for rutin was 0.05-50 μM with a detection limit of 0.005 μM (S/N = 3). The ternary nanocomposite sensor also exhibited good reproducibility and stability, and was successfully used for the simultaneous determination of myricetin and rutin in real orange juice samples with recoveries ranging between 100.57% and 108.46%. Keywords: Ternary nanocomposite, Simultaneous determination, Electrochemical sensor, Myricetin, Rutin